Pengaruh Audit Tenure dan Auditor Switching Pada Audit Delay Dengan Financial Distress Sebagai Variabel Pemoderasi - Pradnyaniti, Luh Putu Yanti; Suardikha, I Made Sadha (E-Jurnal Akuntansi; Vol 26 No 3 (2019)DO - 10.24843/EJA.2019.v26.i03.p16, 2019)
This study aims to obtain empirical evidence of the effect of audit tenure and auditor switching on audit delay with financial distress as a moderating variable. The method of determining the sample used was purposive sampling. The number of samples obtained is 23 mining companies in BEI 2013-2017. The analysis techniques used is the Moderated Regression Analysis (MRA) test. Based on the results of the study, it is known that audit tenure has a negative effect on audit delay. Switching auditors have no effect on audit delay. Financial distress weakens the effect of audit tenure on audit delay. Financial distress is not moderate the effect of auditor switching on audit delay. The theoretical implications of this research are in addition to references to further research regarding research relating to audit delay and signal theory and compliance theory. Keywords : Audit delay, audit tenure, auditor switching, financial distress